Effect of substrate heating and microwave attenuation on the catalyst free growth and field emission of carbon nanotubes. (November 2015) - Kar, R.; Sarkar, S.G.; Basak, C.B.; Patsha, Avinash; Dhara, Sandip; Ghosh, Chanchal; Ramachandran, Divakar; Chand, N.; Chopade, S.S.; Patil, D.S.
Abstract: Carbon nanotubes (CNTs) have been directly grown on Inconel 600 substrates by microwave plasma enhanced chemical vapor deposition without using any external catalyst. Grown CNTs were characterized by field emission scanning electron microscopy, high resolution transmission electron microscopy, X-ray diffraction, Raman spectroscopy and field emission measurements. Characterization results show that field emission current density increases from 200 μA/cm 2 at ∼5.5 V/μm to 14.5 mA/cm 2 at ∼1.6 V/μA when substrate is heat-treated and incident microwave is attenuated before reaching it. Detailed characterization reveals that heat-treatment results in migration of Cr and Fe oxides towards the top surface which completely changes substrate morphology also. Microwave attenuation reduces reflection of microwaves from the substrate and increases residence time of the precursor over the substrate promoting high density growth of CNTs. The combination of these two process parameters resulted in growth of long, dense CNTs with bamboo-like defects that contributes to enhanced current density at lower applied field.